Agreement of zero-heat-flux thermometry compared with infrared tympanic temperature monitoring in adults undergoing major surgery - Jingyan Wang; Hao Liang; Congzhe Tian; Guiyuan Rong; Xinfeng Shao; Cheng Ran (European Journal of Medical Research)
Abstract The patient’s body temperature significantly fluctuates, affected by factors, including anesthesia. The ideal temperature monitoring method that is suitable for perioperative application is of great significance for identifying hypothermia and malignant hyperthermia early, as well as for guiding intraoperative temperature protection. This study aims to compare the cutaneous zero-heat-flux (ZHF) thermometer application in general anesthesia using the infrared tympanic measurement as a reference. We conducted a prospective observational study and enrolled 130 patients scheduled for major surgery with general anesthesia. A forehead ZHF sensor (Tzhf) and an infrared tympanic thermometer (Ttym) were used to continuously measure core temperature. We assessed the agreement using Bland–Altman analysis and concordance correlation coefficient, comparing the paired measurement of Tzhf and Ttym. We further calculated the percentage of difference within 0.5 ℃ between the two devices. Sensitivity, specificity, and predictive values were estimated to interpret the performance of the ZHF thermometer in detecting hypothermia and hyperthermia. The analysis involved 1626 pairs of measurements for the comparison. The mean difference between the ZHF and the tympanic measurements was 0.11 ℃ ± 0.27 ℃, 93.5% of the measurements differences fell within ± 0.5 ℃. Tzhf was significantly correlated with Ttym (r = 0.90). The ZHF thermometry detected the presence of Ttym hypothermia with sensitivity and specificity of 0.89 and 0.88, respectively. Temperature monitoring with the ZHF thermometer indicates a good agreement with the infrared tympanic measurement and a high performance for detecting intraoperative hypothermia.